2009
DOI: 10.1177/070674370905401206
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Postpartum Practices and Rituals: Clinical Implications

Abstract: In many cultures, postpartum rituals are observed because they are believed to have beneficial mental health effects. Our systematic review examines the research literature investigating the effects of postpartum rituals on postpartum depression (PPD) to determine if the rituals protect against PPD. Methods: MEDLINE, CINAHL, PsycINFO, EMBASE, and the Cochrane Library were searched (from 1966 to October 31, 2008). Reference lists of relevant articles and links to related articles were also examined. Both qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
(42 reference statements)
0
33
0
Order By: Relevance
“…Whilst it is understandable that the process of translation of the instruments and attempts to maintain the homogeneity of the interpretation of the questions had been considered, some cultures may define unique clusters of symptoms that differ from the western concept of PND [159] . Malaysia, a multi-ethnic country located in Southeast Asia comprises of three main races, including Malay (53.3%), Chinese (26.0%) and Indian (7.7%) [160] .…”
Section: Discussionmentioning
confidence: 99%
“…Whilst it is understandable that the process of translation of the instruments and attempts to maintain the homogeneity of the interpretation of the questions had been considered, some cultures may define unique clusters of symptoms that differ from the western concept of PND [159] . Malaysia, a multi-ethnic country located in Southeast Asia comprises of three main races, including Malay (53.3%), Chinese (26.0%) and Indian (7.7%) [160] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by , Jordanian women defined postpartum care in terms of strong family support and kinship, and preservation of childbearing customs as expressed in the celebration of the birth of the baby. These rituals were found to be of supportive value and helped to facilitate transition to motherhood (Dennis et al, 2007;Grigoriadis et al, 2009).…”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…Social support can come in many forms. In China, Japan, and Malaysia, the traditional "confinement" practices aim to help new mothers recover from pregnancy and childbirth (Cheng, Fowles, & Walker, 2006;Grigoriadis et al, 2009). The mother, receiving help from her family, remains at home for 30 days to rest and avoids physical work, which aids in the recovery of her physical annually on childbirth (Stalls, 2013), yet America has a higher infant mortality rate than 28 other developed countries (Ohio Department of Health, 2009).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Despite an inconsistent definition of the social support construct in research, the philosophy of societal involvement was the predominant theme addressed among researchers across the globe. Grigoriadis et al (2009) conducted a systematic review of multiple postpartum practices that transcended nine countries to determine if these practices protected against PPD. The authors reported that appropriate support may be of some protective value, which was more important than the specific ritual/practice itself.…”
Section: Review Of Literaturementioning
confidence: 99%